Clinical Presentation and Histopathological Assessment of Acalculous Cholecystitis (Medical Forum Monthly, 2024)
Objective: To determine the clinical pattern and histopathological assessment in patients with acalculous cholecystitis.Study Design: Descriptive case series studyPlace and Duration of Study: This study was conducted at the all units of General Surgery, LUMHS, Jamshoro from January 2016 to July 2016.Materials and Methods: Patients after diagnosis of acalculous cholecystitis through ultrasound were incorporated in the study. Patients were selected from OPD of general surgery and admitted for the cholecystectomy. Surgeries were carried out by senior general surgeons with more than 5 year experience. After surgeries all the specimen of the removal gall bladder, were sent to the laboratory from all the cases for the histopathological assessment.Results: This study contains 49 cases with diagnosis of acalculous cholecystitis, mean age was 43.12+4.23 years. Females were found most common 59.19%. Right upper quadrant pain was the most common in 92% of the cases, following by epigastrium pain, fatty food intolerance, nausea and vomiting and others as well as feeling fatigue and abdominal discomfort were found with percentage of 51.02%, 12.24%, 30.61% and 20.40% respectively. Chronic cholecystitis was the most common histological finding in 57.14% patients, acute cholecystitis was found in 15.32%, Xanthogranulomatous cholecystitis was in 10.20%, gangrenous cholecystitis was in 4.08%, while malignancy was found only in 1 case and 2 cases were without pathology.Conclusion: Female gender is more associated with acalculous cholecystitis; most common clinical presentation was right upper quadrant pain and most prevalent histopathological finding was the chronic cholecystitis and carcinoma was very low only in one case.